Xanthogranulomatous endometritis: a benign mimicker of malignancy - Chandramouli, Roshni; Rajan, Niranjana; Veerappan, Venkatachalam; Venkatesan, Dhanalakshmi; Balasundaram, Partheeban (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Xanthogranulomatous endometritis is a pathological entity which has an unusual characteristic of partial or complete replacement of the mucosa by granulation tissue with plenty of foamy histiocytes, sidero blasts and multinucleated giant cells. This condition clinically and radiologically mimics an endometrial carcinoma, which might create panic in patients as well as healthcare professionals. Hence it is important for Gynaecologists and pathologists to be aware of this condition so as to differentiate it from malignancy. Coexisting malignancy too is a possibility to be ruled out. We report case of a 69-year-old for whom we had high suspicion for malignancy based on clinical and radiological features, hence surgical oncologist opinion was obtained and total laparoscopic hysterectomy+bilateralsalpingo-oophorectomy and frozen section was performed-reported as inflammatory reaction. Hence, further oncological procedure (lymphadenectomy and omentectomy) was abandoned. The final Histopathology was reported as xanthogranulomatous endometritis. We are publishing this case report due to rarity(<30 cases reported worldwide) and its close resemblance to malignancy clinically and radiologically.